2023
DOI: 10.3390/ijms24097923
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Analyses of Cuproptosis-Related lncRNAs in Pancreatic Adenocarcinoma, with a Focus on the Molecular Mechanism of LINC00853

Abstract: Pancreatic cancer (PC) is a deadly malignant digestive tumor with poor prognoses and a lack of effective treatment options. Cuproptosis, a recently identified copper-dependent programmed cell death type, has been implicated in multiple cancers. Long non-coding RNAs (lncRNAs) are also linked to the progression of PC. However, the role and prognostic values of cuproptosis-related lncRNAs in pancreatic adenocarcinoma (PAAD) remain unclear. In this study, we systemically analyzed the differential expressions and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Studies have shown that products of glycolysis can regulate the activity of disulfidptosis and cuproptosis pathways, thus impacting the fate of tumour cells [11,13,18]. These findings identify the significant role of glycolysis in tumour cell metabolism, underscoring the importance of investigating the interplay between disulfidptosis and cuproptosis for a better understanding of the molecular mechanisms underlying tumour cell metabolism and programmed cell death processes.…”
Section: Discussionmentioning
confidence: 84%
“…Studies have shown that products of glycolysis can regulate the activity of disulfidptosis and cuproptosis pathways, thus impacting the fate of tumour cells [11,13,18]. These findings identify the significant role of glycolysis in tumour cell metabolism, underscoring the importance of investigating the interplay between disulfidptosis and cuproptosis for a better understanding of the molecular mechanisms underlying tumour cell metabolism and programmed cell death processes.…”
Section: Discussionmentioning
confidence: 84%
“…4; Table 3). The cuproptosis-related lncRNA LINC00853 significantly enhances cellular glycolysis and cell proliferation in pancreatic cancer (PC) cells by PFKFB3 and increases the level of cellular mitochondrial respiration and tumor growth rate [102]. Meanwhile, another cuproptosisrelated lncRNA, CASC8, is highly expressed in PC, making the prognosis of PC worse.…”
Section: Epigenetic Modifications In Cuproptosismentioning
confidence: 99%